Efficacy of Dihydroartemisinin-piperaquine compared to Artesunate-Mefloquine in treating uncomplicated falciparum malaria in adults and children: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Nabahat Shafi, Maryam Abdul Rab, Syed Ibad Ali, Muhaddisa Batool. (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Malaria is a vector-borne disease. Artemisinin-based combination therapies (ACTs) are used in the treatment of malaria. Among ACTs, DHAP and AM are two widely used regimens. Currently, no credible literature has been presented in the past five years that compares them. Objective: To evaluate the efficacy of Dihydroartemisinin-piperaquine (DHAP) compared to Artesunate-Mefloquine (AM) in treating uncomplicated falciparum malaria in adults and children. Materials and Methods: Our study evaluates the efficacy of DHAP versus AM for treating uncomplicated falciparum malaria in children and adults. Only randomized controlled trials (RCTs) were included. A comprehensive search of PubMed, Cochrane Central, and ClinicalTrials.gov was conducted, and data were screened using Rayyan. Primary outcome (efficacy); secondary outcomes (dizziness, abdominal discomfort, sleep disturbances) were included. Risk of bias was assessed via the Cochrane tool (low risk). Data were analyzed using Review Manager with a random effects model. Results: Out of 196 RCTs, 5 were included. No statistically significant difference in efficacy regarding symptom improvement was found between DHAP and AM [RR 1.00 (95% CI: 0.98-1.01, p=0.67)]. Adverse effects varied, with dizziness [RR 0.25 (95% CI: 0.17-0.38, p=<0.00001) and sleep disturbances [RR 0.53 (95% CI: 0.28-1.01, p=0.05] more common in the AM group, while abdominal discomfort [RR 0.84 (95% CI: 0.56-1.25, p=0.78)] was similar. Studies showed a low risk of bias. Conclusion: DHAP is as effective as AM. Study limitations include only 5 RCTs and some level of heterogeneity. Future studies with larger patient populations are necessary. Keywords: Dihydroartemisinin-piperaquine, Artesunate-Mefloquine, Malaria treatment, Efficacy, Adults and children.